Perlakuan Enzim pada Serpih Kayu Daun Lebar untuk Refiner Mechanical Pulping (RMP) Enzymatic Pretreatment of Hardwood Chips for Refiner Mechanical Pulping (RMP) Process - Wawan Kartiwa Haroen (Masyarakat Peneliti Kayu Indonesia, 2009)
The objective of the study is to examine the influence of 10 l/ ton of Xylanase and Lypase pretreatment on biomechanical pulp of Gmelina and Paracerianthes wood chips with Refiner Mechanical Pulping (RMP) process. The result shows that the enzymatically pretreated of chips can save the electrical consumption of the refiner machine up to 30%, while reducing of 45 50% extractives, and significant improvement of the pulp physical properties compared with control. Two stages of P1 and P2 hydrogen proxide pulp bleaching produced pulp brightness of 65 71.9 % ISO and more than 97% yield bleached pulp. Physical properties of the tensile index and burst index testing result of Gmelina and Paracerianthes mechanical pulp sheet are fairly good.